Implementasi Prinsip-Prinsip Manajemen Mutu di SMA Negeri 1 Pangkalan Lada - Khafidhoh, Khafidhoh; Siminto, Siminto (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2025)
Quality management has become a very crucial thing along with the development of technology and the demands of society for quality education services. Quality education is the goal of all educational institutions in accordance with the expectations of the surrounding community and in line with the goals of national education. The purpose of this study is to determine how the implementation of quality management principles in the educational institution of SMA Negeri 1 Pangkalan Lada is carried out. This study was conducted by reviewing or reviewing the literature in depth and conducting case studies. Case studies were carried out using observation, interview, and documentation methods. The results of this study illustrate that the implementation of quality management principles in SMA Negeri 1 Pangkalan Lada was carried out effectively, could create a learning environment that favors students, improve the quality of education, and optimize the involvement of all education stakeholders.